2015
DOI: 10.4137/jcd.s30596
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Spatial Learning Memory after Isoflurane Anesthesia or Appendectomy in Aged Mice is Associated with Microglia Activation

Abstract: Postoperative cognitive dysfunction (POCD) has been one of the most common problems in elderly patients following surgery. But the specific mechanism of POCD is still not clear. To further understand the reason of these postoperative behavioral deficits, we evaluated the spatial learning memory of both adult (3 months) and aged (18 months) male mice, 3 or 28 days after isoflurane (Iso) exposure for two hours or appendectomy (App). Hippocampal microglia activation and IL-1β, TNF-α, and IFN-γ expression were als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 58 publications
1
34
0
Order By: Relevance
“…CNS inflammation is one of the main causes of POCD, and over-activation of microglia might be an important link leading to CNS inflammation. 16 Several studies have shown that microglia hyper-activation can be stained with immunohistochemistry and labeled with iba1. 17 In this experiment, microscopic observation revealed that the number of iba1-labeled activated microglia in laparotomy group was remarkably increased than that of the sham control group.…”
Section: Discussionmentioning
confidence: 99%
“…CNS inflammation is one of the main causes of POCD, and over-activation of microglia might be an important link leading to CNS inflammation. 16 Several studies have shown that microglia hyper-activation can be stained with immunohistochemistry and labeled with iba1. 17 In this experiment, microscopic observation revealed that the number of iba1-labeled activated microglia in laparotomy group was remarkably increased than that of the sham control group.…”
Section: Discussionmentioning
confidence: 99%
“…Although anesthesia can result in negative effects during development, such as apoptotic neurodegeneration, deficits in hippocampal synaptic functions, and persistent behavioral and cognitive impairments (Jevtovic‐Todorovic et al, ; Jevtovic‐Todorovic, Boscolo, Sanchez, & Lunardi, ; Loepke et al, ), few studies have investigated neural and behavioral deficits that may extend into adulthood (Cao et al, ; Li, Li, et al, ; Mawhinney et al, ; Wang, Ma, Fang, Xue, & Liao, ). Mature brains may have a distinctive pathophysiological response to isoflurane compared to younger, developing brains, with differences observed in neurogenesis, neuronal differentiation, and cognitive outcomes after anesthesia (Stratmann et al, ; Zhu et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Ma et al [22] demonstrated that TNF- α , IL-1 β , IL-4, and IL-6 in the hippocampus increased after surgery and the TNF- α receptor antagonist attenuated the elevation of these cytokines. Wang et al [23] found that the hippocampal IL-1 β , TNF- α , and IFN- γ were overexpressed after surgery in aged mice. Hovens et al [24] demonstrated that the hippocampal IL-6, IL-12, and IL1 β increased after surgery in aged rats.…”
Section: Discussionmentioning
confidence: 99%